2016
DOI: 10.3402/tellusa.v68.31051
|View full text |Cite
|
Sign up to set email alerts
|

How northern freshwater input can stabilise thermohaline circulation

Abstract: A B S T R A C TThe North Atlantic thermohaline circulation (THC) carries heat and salt towards the Arctic. This circulation is partly sustained by buoyancy loss and is generally believed to be inhibited by northern freshwater input as indicated by the 'box-model ' of Stommel (1961). The inferred freshwater-sensitivity of the THC, however, varies considerably between studies, both quantitatively and qualitatively. The northernmost branch of the Atlantic THC, which forms a double estuarine circulation in the Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…These general ideas have been extended further by considering the Arctic Mediterranean to be a double estuary (Eldevik & Nilsen, ; Lambert et al, ). This conceptualizes cooling and dense‐water formation in the Nordic Seas as a negative estuary and positive buoyancy forcing (freshwater input) in the Arctic Ocean (i.e., a positive estuary).…”
Section: The Circulation Of Atlantic Water In the Arcticmentioning
confidence: 99%
See 1 more Smart Citation
“…These general ideas have been extended further by considering the Arctic Mediterranean to be a double estuary (Eldevik & Nilsen, ; Lambert et al, ). This conceptualizes cooling and dense‐water formation in the Nordic Seas as a negative estuary and positive buoyancy forcing (freshwater input) in the Arctic Ocean (i.e., a positive estuary).…”
Section: The Circulation Of Atlantic Water In the Arcticmentioning
confidence: 99%
“…Heat loss in the Nordic Seas drives an overturning circulation there (Mauritzen, ) while the freshwater input to the north drives an estuarine circulation with the Atlantic Water layer. Lambert et al () find that because of the Arctic estuary circulation, an Atlantic Water inflow to the Arctic can persist even in the absence of deep convection in the Nordic Seas. This is an important point in the context of discussions related to Atlantic Water heat entering the Arctic being influenced by the strength of the Atlantic Meridional Overturning Circulation (AMOC).…”
Section: The Circulation Of Atlantic Water In the Arcticmentioning
confidence: 99%
“…The salinity changes in the Baltic depend on the irregular inflow of North Sea water through the Danish Straits and the amount of freshwater runoff, which are in turn controlled by climatic factors in the Atlantic (Hänninen et al, 2000). The Baltic freshwater outflow into the Nordic Seas has a large potential influence on water mass transformation (Lambert et al, 2016(Lambert et al, , 2018Winsor et al, 2001), by enhancing Polar Water outflow and suppressing Deep Water outflow (Lambert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Arctic is characterized by a significant modification of circulating water masses due to freshwater input and by cooling due to surface heat loss (Carmack et al, ; Rudels et al, ). This water mass transformation maintains a steady state circulation of inflowing warm, saline water, and two branches of outflow: one carrying cold fresh water and the other carrying cold dense water (Eldevik & Nilsen, ; Lambert et al, ; Rudels, ; Stigebrandt, ). Besides this steady state circulation, the Arctic exhibits a strong seasonality due to solar irradiance, the formation and melt of sea ice, and river runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jahn, Tremblay, Mysak, et al () found an increase in the northward ocean heat transport with increased Arctic freshwater export. The impact of long‐term changes in Arctic freshwater input may have consequences beyond the Arctic domain, as Lambert et al () suggested that increased Arctic runoff can stabilize the northern branch of the Atlantic thermohaline circulation. Although knowledge of these long‐term impacts is important in light of the projected increase in Arctic river runoff, little is known of the short‐term impacts of runoff variability.…”
Section: Introductionmentioning
confidence: 99%